East European integration and East-West trade - Marer, Paul; Marer, Paul.; Montias, John Michael; Joint Committee on Eastern Europe (Bloomington : Indiana University Press, 1980)
The book is based in part on some of the papers and formal discussions originally presented at the Conference on East European Integration and East-West Trade, held at Indiana University Bloomington in Oct. 1976, and in part on additional studies commissioned after the conference.
Includes bibliographical references and index.
ijb 16/01/2019
Loans
Keywords: International economic integration; Economic integration; East-West trade; Europe, Eastern